Magnetic Field Fiber Specklegram Sensors Based on Tb3+-Doped Magneto-Optical Glasses With High Verdet Constants - Cabral, Thiago D.; Franco, Douglas F. [UNESP]; Fujiwara, Eric; Nalin, Marcelo [UNESP]; Cordeiro, Cristiano M. B. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Optical fiber specklegram sensors (FSSs) for magnetic field measurements are reported. The probes are compact, with only a fiber length of ∼ 100 mm exposed to a magnetic field and comprised of no-core fibers doped with terbium oxide (Tb4O7), so the Verdet constant is dramatically improved in comparison to regular commercial fibers (∼ 20× increase, 10-mol% fiber), greatly enhancing the modulation of the output specklegram. The response to static magnetic fields was evaluated for different concentrations (6-10 mol%) of Tb4O7, yielding an increase in sensitivity of up to 59× ( 8.78× 10-2 mT -1 , 10 mol%) and 6× resolution (1.86× 10-2 mT, 6 mol%) in relation to a regular silica multimode fiber (MMF). A simple setup with a He-Ne laser and inexpensive webcam charge-coupled device (CCD) camera was employed, producing results comparable to fiber sensors based on more complicated setups such as fiber interferometers. To the best of our knowledge, this comprises the first demonstration of highly multimode magnetic field FSS based on magneto-optical (MO) glass to capitalize on both the Faraday rotation and the polarization mode conversion.
Keywords: Faraday rotation; fiber specklegram sensor; magnetic field measurement; optical fiber sensors (OFS); terbium oxide-doped fiber